A meta-analysis comparing the diagnostic performance of abbreviated MRI and a full diagnostic protocol in breast cancer. Issue 2 (February 2021) - Baxter, G.C.; Selamoglu, A.; Mackay, J.W.; Bond, S.; Gray, E.; Gilbert, F.J.
Abstract : AIM: To undertake a meta-analysis of the diagnostic performance of abbreviated (ABB) magnetic resonance imaging (MRI) and full diagnostic protocol MRI (FDP-MRI) in breast cancer. MATERIALS AND METHODS: This meta-analysis was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis for Diagnostic Test Accuracy (PRISMA-DTA) guidelines. The PubMed and EMBASE databases were searched through August 2019 for studies comparing the diagnostic performance of ABB-MRI and FDP-MRI in the breast. Studies were reviewed by two authors independently according to eligibility and exclusion criteria and split into two subgroups (screening population studies and studies using cohorts enriched with known cancers) to avoid bias. Quality assessment and bias for diagnostic accuracy was determined with Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2). The diagnostic accuracy for each subgroup was pooled using a bivariate random effects model and summary receiver operating characteristic (sROC) curves produced. Sensitivities and specificities were compared using a paired t -test. RESULTS: Five screening (62/2, 588 cancers/patients) and eight enriched cohort (540/1, 432 cancers/patients) studies were included in the meta-analysis. QUADAS-2 assessment showed a low risk of bias in most studies. The pooled sensitivity/specificity/area under the receiver operating characteristic curve (AUC) for screening studies was 0.90/0.92/0.94 for ABB-MRI and 0.92/0.95/0.97 for FDP-MRI. The pooled sensitivity/specificity/AUC for enriched cohort studies was 0.93/0.83/0.94 for ABB-MRI and 0.93/0.84/0.95 for FDP-MRI. There was no significant difference in sensitivity or specificity using ABB-MRI or FDP-MRI ( p= 0.18 and 0.27, p= 0.18 and 0.93, respectively). CONCLUSION: The diagnostic performances of the ABB-MRI and FDP-MRI protocols used in either screening or enriched cohorts were comparable. There was a large variation in patient population, study methodology, and abbreviated protocols reported. Highlights: The diagnostic performance of abbreviated MRI matches standard breast MRI. Few studies investigated abbreviated MRI screening populations alone. The mean examination time of abbreviated MRI is significantly reduced. The abbreviated MRI protocols reported are very varied.